Spring and Autumn Annals of Wu and Yue : An Annotated Translation of Wu Yue Chunqiu - Zhao, Ye, active 40 (Book collections on Project MUSE., 2021)
"Spring and Autumn Annals of Wu and Yue is the first complete English translation of Wu Yue Chunqiu, a chronicle of two neighboring states during China's Spring and Autumn period. This collection of political history, philosophy, and fictional accounts depicts the rise and fall of Wu and Yue and the rivalry between them, the inspiration for centuries of poetry, vernacular fiction, and drama"--